1984
DOI: 10.1104/pp.74.4.749
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast Ultrastructure, Chlorophyll Fluorescence, and Pigment Composition in Chilling-Stressed Soybeans

Abstract: Shoots of 16-day-old soybeans (Glycine max L. Merr. cv Ransom) were chilled to 10°C for 7 days and monitored for visible signs of damage, ultrastructural changes, perturbations in fluorescence of chlorophyll (Chl), and quantitative changes in Chi a and b and associated pigments. Precautions were taken to prevent the confounding effects of water stress. A technique for the separation of lutein and zeaxanthin was developed utilizing a step gradient with the high performance liquid chromatograph. Visible losses i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0
1

Year Published

1987
1987
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 27 publications
1
32
0
1
Order By: Relevance
“…Ultrastructural injury was restricted to the chloroplast (Figs. 5 and 6) which is in agreement with longer term, lower irradiance studies involving other chilling-sensitive plants (15,22,27,31). Of possible significance in the present study is the finding that pea chloroplasts showed signs of ultrastructural alterations (Fig.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Ultrastructural injury was restricted to the chloroplast (Figs. 5 and 6) which is in agreement with longer term, lower irradiance studies involving other chilling-sensitive plants (15,22,27,31). Of possible significance in the present study is the finding that pea chloroplasts showed signs of ultrastructural alterations (Fig.…”
Section: Resultssupporting
confidence: 80%
“…5a), are intriguing. Such changes have been reported previously in chilling-sensitive plants such as Phaseolus vtulgaris and Gossypium hirsutum given a moderate stress of 5°C, 100%RH, and 500 uE-m-s' (31) and Glycine max given 10°C, 85% RH, and 500 ,gE-m-2s' (15). The peripheral vesicles are similar in appearance to components of the chloroplast peripheral reticulum, a system of anastomosing tubules connected to the inner envelope membrane and thought to be involved in metabolite transport (10).…”
Section: Resultsmentioning
confidence: 68%
“…Smillie and Hetherington (17) showed that the maximal rate of the light induced F, rise in heat treated leaves from different species was a useful method for determining relative heat tolerance. F, increases during chilling in the dark have previously been reported (5,6,9); however, chilling in the light often results in a decline in F, (6,10). The temperature dependence of the recovery of PSII F, following illumination in cucumber and pea leaves has been reported by Peeler and Naylor (1 1 …”
mentioning
confidence: 83%
“…At these relatively high temperatures it is unlikely that phenomena like membrane disruption (Rikin et al, 1979;Powles, 1984) and changes in the chloroplast ultrastructure (Taylor and Craig, 1971;Musser et al, 1984;Wise and Naylor, 1987) (table II).…”
Section: Gas Exchangementioning
confidence: 99%